Jinnah : India, partition, independence - Singh, Jaswant, 1938- (New Delhi : Rupa & Co., 2009)
Biography of Mohammed Ali Jinnah, 1876-1948, statesman and founder of Pakistan.
Includes bibliographical references (p. [586]-653) and index.
Keywords: Jinnah, Mahomed Ali, -- 1876-1948.; Statesmen -- Pakistan -- Biography; India -- Politics and government -- 1919-1947.; India -- History -- Partition, 1947.